Dorchester Priory
The proportions of columns were reduced, as confidence in the strength of stone increased. Jointing of stonework became even more exact, and Purbeck marble was safely dispensed with as techniques improved. This column, with shafting integrated with its core, is typically slender and the richly cared stonework has gained plasticity which earlier generations never knew.